Hak Pasien dalam Hukum Kesehatan Perspektif Ahlussunnah Wal Jamaah (Aswaja): Analisis Normatif, Filosofis, dan Etis Berbasis Maqāṣid Al-Syarī‘ah - Faiz Karim Fatkhullah; Putu Yusta Naraswari Kasuma; Abbi Yanto; Fatimah Oktarina; Diyah Eka Pratami (CV. Green Publisher Indonesia, 2026)
Patient rights represent a fundamental element in modern health law systems, ensuring the protection of human dignity, individual autonomy, and the safety of medical services. In Indonesia, the recognition of patient rights gains normative reinforcement through Law No. 17 of 2023 on Health. However, in Indonesia's religious social context, legal legitimacy does not solely derive from positive norms but also from their alignment with religious values. This research aims to analyze the concept and regulation of patient rights in national health law and to examine their relevance from the perspective of Ahlussunnah wal Jamaah (Aswaja) through a maqāṣid al-syarī‘ah approach. This study is a normative juridical research employing statutory, conceptual, and philosophical approaches, using descriptive-prescriptive analysis of primary and secondary legal sources. The research findings indicate that patient rights—such as the right to medical information, informed consent, data confidentiality, and fair services—are substantively aligned with the objectives of Islamic sharia, particularly the protection of life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), and human dignity (karāmah al-insān). Aswaja principles like tawassuṭ (moderation), tawāzun (balance), ta‘ādul (justice), and tasāmuḥ (tolerance) strengthen the ethical legitimacy of implementing patient rights in health service practices. Theoretically, this research contributes to the development of health law based on moderate Islamic ethics by integrating positive legal norms and maqāṣid values as a normative-philosophical foundation in the national health law system. The implications of this research underscore the importance of harmonizing health regulations with Islamic ethical values to build fair, humane, and civilized health services in Indonesia.